2021
DOI: 10.1002/hep.31705
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Techniques and Awaited Clinical Applications for Human Pluripotent Stem Cell Differentiation into Hepatocytes

Abstract: Liver transplantation is currently the only curative treatment for several liver diseases such as acute liver failure, end-stage liver disorders, primary liver cancers and certain genetic conditions.Unfortunately, despite improvements to transplantation techniques, including live donor transplantation, the number of organs available remains insufficient to meet patient needs.Hepatocyte transplantation has enabled some encouraging results as an alternative to organ transplantation, but primary hepatocytes are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 87 publications
(159 reference statements)
0
36
0
Order By: Relevance
“…However, the costs and complex technology involved in establishing and maintaining organoid cultures are causes of the limited research. In addition, the batch effect caused by varying environments and culture durations affect the experimental results (Luce et al, 2021) (Figure 4).…”
Section: Disease Modelsmentioning
confidence: 99%
“…However, the costs and complex technology involved in establishing and maintaining organoid cultures are causes of the limited research. In addition, the batch effect caused by varying environments and culture durations affect the experimental results (Luce et al, 2021) (Figure 4).…”
Section: Disease Modelsmentioning
confidence: 99%
“…Through guided differentiation, human-induced pluripotent stem cells (hiPSCs) offer a reliable source of hepatocytes that are certainly proving themselves useful in numerous tissue engineering and personalized medicine applications [1][2][3][4][5][6]. However, concerns persist regarding the lack of functional maturity and long-term maintenance in culture of hiPSCderived hepatocytes (iHeps).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, iHeps still display a fetal hepatic phenotype rather than an adult one [7,8] and, in particular, they continue to express fetal markers such as α-fetoprotein (AFP), as well as being poor at reproducing key mature functions, such as the activity of many detoxification enzymes [8,9]. Improved protocols and 3D culture systems have shown that the hepatic functions of iHeps can be enhanced, thus contributing to the study of liver development, diseases and the efficacy of medicinal products [3][4][5]10,11], but hepatocytes with adult features have still not been generated. This hurdle currently remains the principal drawback of iHeps in terms of applications where a considerable degree of maturity is required, such as pharmacology/toxicology studies and the development of in vitro systems to model liver physiology and pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, hiPSCs could be a promising renewable and easily accessible cell source for the generation of functional hepatocytes which may obtain full maturity with the application of future biotechnologies. When applied in the bioprinting of hepatic tissue models using proper printing techniques and bioinks, hiPSC-derived hepatocytes (hiPSC-Heps) have demonstrated well-maintained cellular phenotypes and biofunctions[ 25 ]. Bioprinting of hiPSCs and human embryonic stem cells was first reported in 2015 by Faulkner-Jones et al .…”
Section: Introductionmentioning
confidence: 99%